2009
DOI: 10.2486/indhealth.47.50
|View full text |Cite
|
Sign up to set email alerts
|

First Korean Working Conditions Survey: A Comparison between South Korea and EU Countries

Abstract: This report aims to provide an overview of the intensity of work and work satisfaction in Korea by comparing the first Korean Working Conditions Survey with the results of the fourth European Working Conditions Survey in 2005. According to the comparison, Korean workers work longer hours than workers in the majority of EU countries. However, work intensity in the EU 27 was 1.5 times stronger than Korea. In Korea, the rate of violence, bullying and harassment in the workplace is much lower than the EU 27, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 0 publications
1
52
0
2
Order By: Relevance
“…Research has shown an increasing risk of workrelated diseases and accidents in Southeast Asian countries which have experienced rapid industrialization 34) . A recent survey revealed the most often reported work-related symptoms to be muscular pain (shoulder, neck, upper arms and lower extremities) (18.1%), followed by stress (17.9%), backache (16.8%), fatigue (16.7%) and headache (11.2%) 35) . Symptoms associated with occupational stress, such as muscular pains and fatigue, are common in the working population and these symptoms are often associated with psychological variables such as anxiety and depression 36) .…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown an increasing risk of workrelated diseases and accidents in Southeast Asian countries which have experienced rapid industrialization 34) . A recent survey revealed the most often reported work-related symptoms to be muscular pain (shoulder, neck, upper arms and lower extremities) (18.1%), followed by stress (17.9%), backache (16.8%), fatigue (16.7%) and headache (11.2%) 35) . Symptoms associated with occupational stress, such as muscular pains and fatigue, are common in the working population and these symptoms are often associated with psychological variables such as anxiety and depression 36) .…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, a representative sample of the economically active population aged 15 to 64 years, i.e., persons who were either employees or self-employed at the time of the interview, was selected. The study design for both surveys employed multistage random sampling based on the Population and Housing Census 27) . The primary sampling units were the population and housing enumeration district, and these were selected by systematic sampling in proportion to the number of households within the enumeration district.…”
Section: Data Sourcementioning
confidence: 99%
“…We performed secondary analysis of data obtained from the First Korean Working Conditions Survey (KWCS), conducted in 2006 by the Korea Occupational Safety and Health Agency (KOSHA) [Park and Lee, 2009]. The survey population was a representative sample of the economically active population aged 15-64 years (in Korea, the legal work age is 15 years).…”
Section: Data Sourcementioning
confidence: 99%
“…Many large companies have gradually reduced the working week. However, a recent survey revealed that 45% of Korean workers still work more than 48 hr a week [Park and Lee, 2009], and the International Labor Organization (ILO) found that 49.5% of workers in Korea work more than 48 hr a week [Lee et al, 2007]. This is the second highest proportion in the world, after Peru, and outstrips the 10% rate seen in the European Union (EU) and the 22% world average [Lee et al, 2007].…”
Section: Introductionmentioning
confidence: 99%